2015
DOI: 10.1007/s11262-015-1233-6
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterisation of Epstein–Barr virus helicase–primase complex and its accessory protein BBLF2/3

Abstract: The helicase-primase complex is part of the lytic DNA replication machinery of herpesviruses, but up to now, almost nothing is known about its structure. For Epstein-Barr virus it consists in the helicase BBLF4, the primase BSLF1 and the accessory protein BBLF2/3. The accessory protein shows only weak sequence homology within the herpesvirus family but may be related to an inactive B-family polymerase. BSLF1 belongs to the archaeo-eukaryotic primase family, whereas the helicase BBLF4 has been related either to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The main results indicate that siRNAs targeting three sites-U77 (a component of the helicase-primase complex HP1), U51 (a G protein-coupled receptor), and U12 (a G protein-coupled receptor-like protein)-significantly reduce the copy number of PCMV. This finding suggested that these three sites are important and conserved targets for PCMV replication, with the G protein-coupled receptor being of interest in murine cytomegalovirus and the component of the helicase-primase complex being associated with the lytic DNA replication machinery of herpesviruses [21,22]. Interfering with their expression or function can effectively inhibit virus replication, providing new insights and methods for the prevention and treatment of PCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The main results indicate that siRNAs targeting three sites-U77 (a component of the helicase-primase complex HP1), U51 (a G protein-coupled receptor), and U12 (a G protein-coupled receptor-like protein)-significantly reduce the copy number of PCMV. This finding suggested that these three sites are important and conserved targets for PCMV replication, with the G protein-coupled receptor being of interest in murine cytomegalovirus and the component of the helicase-primase complex being associated with the lytic DNA replication machinery of herpesviruses [21,22]. Interfering with their expression or function can effectively inhibit virus replication, providing new insights and methods for the prevention and treatment of PCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The main results indicate that siRNAs targeting three sites-U77 (a component of the helicase-primase complex HP1), U51 (a G protein-coupled receptor), and U12 (a G protein-coupled receptor-like protein)-significantly reduce the copy number of PCMV. These findings suggested that these three sites are important and conserved targets for PCMV replication, with the G protein-coupled receptor being of interest in murine cytomegalovirus and the component of the helicase-primase complex being associated with the lytic DNA replication machinery of herpesviruses [39,40]. Interfering with their expression or function can effectively inhibit virus replication, providing new insights and methods for the prevention and treatment of PCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the expression of both Zta and Rta proteins is always required for subsequent expression of lytic early proteins [ 41 ] such as BMRF1, SM, BHLF1, and BHRF1. Additionally, viral DNA polymerase (BALF5) [ 42 ], the DNA polymerase processivity factor (BMRF1) [ 43 ], the viral helicase (BBLF4) [ 44 ], and viral primase (BSLF1) [ 44 ], among others are currently expressed at this stage. BMRF1 and BRRF1 are transcription factors that activate the oriLyt (Lytic replication origin).…”
Section: Epstein-barr Virus: Structure and Replicative Cyclementioning
confidence: 99%